Lifestyle Risk Factors Increasing the Prevalence of Hypertension in Women of Reproductive Age in Metro City, Indonesia: A Community-Based Case Control Study - Sofia, Meta; Riyanto, Riyanto; Udani, Giri; Lebuso, Mapitso (Jurnal Kesehatan Metro Sai Wawai, 2024)
Introduction: The prevalence of hypertension is still a global health problem, and efforts have been made to control and prevent it, including in Indonesia. However, the trend of high prevalence of hypertension and healthy lifestyle has not indicated a significant decrease, including in women of reproductive age. Objective: This study is to evaluate the lifestyle factors associated with the incidence of hypertension in women of reproductive age, so that evidence base practice can be used in prevention and control efforts. Methods: Observational study with case control design involving women of reproductive age with hypertension in Yosomulyo Primary Health Care, Metro city. Case group and control group with a ratio of 26: 26 were selected by consecutive sampling technique that fulfilled the research requirements. Hypertension data was collected using a digital tensimeter, while lifestyle factors data was collected using a questionnaire tool that has been tested for validity and reliability. The chi square test was used to prove the relationship between lifestyle risk factors and hypertension. Results: The results showed that lifestyle factors associated with women of reproductive age were obesity (OR=5.127; p=0.012), high sodium consumption (OR=14.00; p=0.000), experiencing stress (OR=8.80; p=0.002), and the use of hormonal contraception (OR=7.50; p=0.021). Meanwhile, exercise activity had no statistical association (p-value 0.404). Conclusion: Unhealthy lifestyle factors, such as obesity, excessive sodium consumption, stress and prolonged use of hormonal contraceptives increase the incidence of hypertension in women of reproductive age. Strengthening healthy lifestyle efforts by increasing education on hypertension risk factors to women of reproductive age is important for the prevention and control of hypertension. Pendahuluan: Masalah prevalensi hipertensi masih menjadi masalah kesehatan global, termasuk Indonesia telah dilakukan upaya pengendalian dan pencegahan. Namun, trend tingginya prevalensi hipertensi dan pola hidup sehat belum mengindikasikan penurunan yang signifikan, termasuk pada wanita usia subur (WUS). Tujuan: Mengevaluasi factor-faktor pola hidup yang berhubungn dengan kejadian hipertensi pada WUS, sehingga dapat digunakan evidence base practise dalam upaya pencegahan dan pengendalian. Metode: Studi observasional dengan rancangan case control melibatkan wanita usia subur dengan hipertensi di Pelayanan Kesehatan Primer Yosomulyo, kota Metro. Kelompok kasus dan kelompok control dengan perbandingan 26 : 26 yang dipilih dengan teknik consecutive sampling yang memenuhi syarat penelitian. Data hipertensi menggunakan tensimeter digital, sedangkan data factor-faktor pola hidup dikumpulkan menggunakan alat kuesioner yang telah diuji validitas dan reabilitas. Uji chi square digunakan untuk membuktikan hubungan faktor risiko pola hidup dengan hipertensi. Hasil: Hasil penelitian menunjukkan bahwa factor pola hidup yang berhubungan dengan wanita usia subur adalah obesitas (OR=5,127; p= 0,012), konsumsi tinggi natrium (OR=14,00; p=0,000), mengalami stress (OR=8,80; p=0,002), dan penggunaan kontrasepsi hormonal (OR=7,50; p=0,021). Sedangkan, aktivitas olahraga tidak ada hubungan secara statistik (p-value 0,404). Simpulan: Faktor pola hidup yang tidak sehat, seperti obesitas, konsumsi natrium berlebihan, stress dan lama penggunaan kontrasepsi hormonal meningkatkan kejadian hipertensi pada wanita usia subur. Penguatan upaya pola hidup sehat dengan peningkatan edukasi factor-faktor risiko hipertensi kepada wanita usia subur penting dilakukan untuk pencegahan dan pengendalian hipertensi